The Effectiveness of the One RW One Health Worker (R1N1) Program in Fulfilling Public Health Services in Surabaya City: Case Study at Mojo Health Center - Gabriel Angelina; Aisyah Retno Octavia; Azizah Putri Rizky Wulandari; Rizky Nurhidayat Perdana (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The One RW, One Health Worker (R1N1) program is a community-based health service innovation launched by the Surabaya City Government in 2024 to expand access to basic health services for the public. This study aims to analyze the program's effectiveness in improving health services at the neighborhood level, using a case study in the working area of the Mojo Community Health Center (Puskesmas). The research uses a descriptive qualitative method, with data collected through in-depth interviews and observation. The analysis applies program effectiveness theory, which includes five indicators: understanding of the program, target accuracy, timeliness, goal achievement, and tangible impact. The results show that the R1N1 program is quite effective in making health services more accessible to the community and raising awareness about the importance of routine health checkups. However, the program still faces challenges, such as a limited number of health workers, unequal facilities at neighborhood halls, and a lack of specific, measurable achievement indicators. This study recommends strengthening the distribution of health workers, improving infrastructure, and establishing more concrete performance indicators to enhance the program's sustainability and effectiveness in the future.